Pengaruh Kualitas Pelayanan Terhadap Minat Berkunjung ke Rumah Makan Payakumbuh Veteran Bintaro - Hendradewi, Savitri; Sukma, Braja Eka; Achmadi, Mochamad (Program Pascasarjana STIE Amkop Makassar, 2024)
This research aims to analyze the influence of service quality dimensions on customer interest in returning to the Veteran Payakumbuh Bintaro Restaurant. The background to this research is driven by the importance of service quality in the culinary industry to increase customer satisfaction and build loyalty. This research uses a quantitative approach with a multiple regression method involving four independent variables (responsiveness, assurance, empathy, physical evidence) and one dependent variable, namely interest in returning to visit. Data collection was carried out by distributing questionnaires with a Likert scale to 100 respondents selected by accidental sampling. The research results show that all dimensions of service quality have a significant influence on intention to revisit, with responsiveness having the greatest influence. The variables of assurance, empathy and concrete evidence also contribute significantly to increasing customer interest in returning. Based on these findings, it is recommended that restaurant managers increase staff responsiveness, provide assurance and empathy training, and ensure that the physical condition of the restaurant is always maintained. Customers are encouraged to provide constructive feedback and create a positive experience during their visit. Thus, good service quality can strengthen customer loyalty and increase the frequency of return visits.